Lithium metal composite negative electrode, preparation method thereof and solid-state battery

By setting a three-dimensional graphene space layer on the surface of the lithium metal negative electrode, the problems of uneven deposition of lithium ions and growth of lithium dendrites are solved, and the circulation performance and safety of lithium metal batteries are improved.

CN119725389APending Publication Date: 2025-03-28CHINA ENERGY LITHIUM +1

Patent Information

Application Number
CN202510232134.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Lithium ions are unevenly deposited during charging and discharging of lithium metal batteries, resulting in the growth of lithium dendrites, piercing the separator and causing safety accidents, and reacting with solid electrolytes to consume lithium ions, reducing battery capacity.

Method used

A three-dimensional graphene space layer is arranged on the surface of the lithium metal negative electrode to form a stable three-dimensional honeycomb skeleton structure, regulate lithium ion deposition, inhibit lithium dendrites, and act as an artificial SEI protective layer to isolate lithium from contact with solid electrolyte.

Benefits of technology

It realizes uniform deposition of lithium ions, reduces dendrite generation and growth, alleviates lithium metal expansion, improves the circulation performance and safety of the battery, and is suitable for liquid and solid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725389A_ABST
    Figure CN119725389A_ABST
Patent Text Reader

Abstract

The invention provides a lithium metal composite negative electrode, a preparation method thereof and a solid-state battery. The lithium metal composite negative electrode is of a three-layer structure and sequentially comprises a current collector, an active substance layer and a graphene space layer, the active substance layer is a lithium metal and / or lithium alloy layer, and the graphene space layer comprises three-dimensional graphene, lithium salt, a binder and a hydrophilic additive. In the space layer, the three-dimensional graphene is a novel carbon nanomaterial, the excellent characteristics of super-large specific surface area and super-high conductivity of the graphene are maintained, the pi-pi acting force between graphene sheet layers is overcome, the stability of a macrostructure is maintained, and the three-dimensional graphene serves as a space layer material to effectively store lithium ions and regulate and control lithium ion deposition; and the cycle and rate performance of the solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium metal batteries, and in particular to a lithium metal composite negative electrode and a preparation method thereof, and a solid-state battery. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles because of their high energy density, high power and long life. At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite, but its theoretical specific capacity is only 372mAh / g, which is far from meeting people's needs. The theoretical specific capacity of lithium metal negative electrode is 3860mAh / g, which is more than 10 times the theoretical specific capacity of graphite. If lithium metal negative electrode can be successfully applied to lithium-ion batteries, the energy density of the battery will be greatly improved, solving the bottleneck faced by the current development of lithium-ion batteries. However, there are some problems that cannot be ignored in the process of repeated use of lithium metal negative electrode. For example, due to the large volume expansion and contraction of lithium metal during the charging and discharging process, it will cause damage to the diaphragm during the cycle, and finally reduce the cycle stability and safety of the battery; when the current density increases, the large lithium metal deposition rate will form dendrites, which will then pierce the diaphragm and cause safety accidents. Therefore, how to safely apply lithium metal negative electrode to lithium batteries is a hot issue of common concern in academia and industry.

[0003] CN119181765A discloses a negative electrode sheet and its preparation method and application, wherein a protective layer is arranged on the active material layer, and the protective layer includes a heat-expandable high molecular polymer substrate and a metal peroxide distributed in the heat-expandable high molecular polymer substrate. The protective layer can inhibit the formation of lithium dendrites, isolate the contact between the positive and negative electrodes, solve the internal short circuit problem, and improve the safety performance of the battery. However, the protective layer of this invention does not have a three-dimensional porous structure, cannot regulate and store lithium ion deposition, and only enhances the mechanical strength of the interface and inhibits the growth of dendrites. Summary of the invention

[0004] The present invention aims to solve the following technical problems: During the charging process of lithium metal batteries, lithium ions migrate from the positive electrode to the negative electrode and deposit at the interface of the negative electrode. They are prone to uneven deposition, thereby growing lithium dendrites. Lithium dendrites continue to grow during the battery cycle, puncture the diaphragm or solid electrolyte in liquid batteries or solid batteries, and the battery is prone to short circuit. At the same time, lithium metal is highly active and reacts with a variety of solid electrolytes. The side reactions consume lithium ions, reduce the capacity of the battery, and affect the electrical performance of the battery. Therefore, it is necessary to set a protective layer on the surface of the lithium metal negative electrode to achieve the regulation of lithium ion deposition, inhibit lithium metal expansion and lithium dendrite growth, improve the affinity of lithium metal with a variety of electrolytes, and reduce the occurrence of side reactions.

[0005] The inventors found that three-dimensional graphene is a new type of carbon nanomaterial composed of two-dimensional graphene on a macroscopic scale. It can overcome the π-π force between graphene sheets while maintaining the excellent characteristics of graphene's ultra-large specific surface area and ultra-high conductivity, effectively blocking the self-disordered stacking of graphene sheets and thus achieving the stability of its macroscopic structure. There are many forms of three-dimensional graphene. The current three-dimensional graphene materials are mostly gel materials with a three-dimensional porous network structure, with multiple active sites, which can effectively improve the lithium ion transmission channel. As a lithium metal negative electrode interface space layer, it can store lithium ions in a three-dimensional space, realize the uniform deposition of lithium ions on the three-dimensional graphene, and improve the battery's cycle and rate performance.

[0006] Specifically, the present invention provides a lithium metal composite negative electrode, characterized in that the negative electrode comprises an active material layer and a graphene space layer arranged on and in contact with the active material layer, wherein the active material layer is a lithium metal and / or lithium alloy layer; the graphene space layer is a layer of a three-dimensional porous structure comprising three-dimensional graphene, a lithium salt, a binder and a hydrophilic additive, wherein the three-dimensional graphene has a honeycomb skeleton structure, and the pore size of the three-dimensional graphene in the graphene space layer is 1-500nm, and the specific surface area is 500-5000m 2 / g, and a yield strength of 10-50MPa; the thickness of the graphene space layer is 1-100μm, and the Young's modulus is ≥6GPa.

[0007] Optionally, the lithium salt includes any one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium difluorooxalatoborate, lithium dimethyl borate, lithium bis(fluorosulfonyl imide), lithium tetrafluoroborate, lithium difluorophosphate, and lithium 4,5-dicyano-2-trifluoromethylimidazole, or a combination of at least two thereof.

[0008] Optionally, the binder includes one or a combination of at least two of polyvinyl alcohol, polyethylene oxide, polybutylene styrene, polystyrene butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxycellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and their derivatives.

[0009] Three-dimensional graphene materials have excellent active material loading and extremely high conductivity. Combined with lithium salts and binders, they can construct a stable three-dimensional honeycomb skeleton structure, providing a large number of active sites for the transmission of lithium ions. The porous structure provides channels for ion transfer during the electrode reaction, assists lithium ion migration, promotes the dissociation of lithium salts, and improves battery cycle performance.

[0010] Optionally, the hydrophilic additive includes a thickener and a modifier;

[0011] The thickener includes one or more of carboxymethyl cellulose, sesbania gum, sodium starch phosphate, triethyl phosphate, and sodium polyacrylate;

[0012] The modifier includes one or more combinations of polyethylene glycol, polyvinyl alcohol, polyoxyethylene ether, carboxylates, sulfonates, sulfate esters, phosphate esters, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.

[0013] Optionally, the mass ratio of the three-dimensional graphene material, lithium salt, binder and hydrophilic additive is (1-20): (1-5): (1-5): (0.5-2), preferably (5-10): (2-3): (1-3): (0.5-1).

[0014] Optionally, the active material layer includes a metal lithium layer, a lithium alloy layer, or a combination of the two; preferably, the lithium alloy layer includes an alloy of lithium and one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt.

[0015] Optionally, the thickness of the active material layer is 3 μm-300 μm, preferably 10 μm-100 μm.

[0016] Optionally, the thickness ratio of the graphene space layer to the active material layer is (0.001-1):1, preferably (0.01-0.1):1.

[0017] Optionally, the lithium metal composite negative electrode also includes a current collector, and the current collector includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and an organic fiber film with a metal plated surface.

[0018] Another aspect of the present invention provides a method for preparing the lithium metal composite negative electrode as described above, the method comprising:

[0019] (1) preparing three-dimensional graphene materials, drying and dehumidifying the three-dimensional graphene, lithium salt, binder, and hydrophilic additive;

[0020] (2) Weigh corresponding proportions of three-dimensional graphene and lithium salt, mix them, refine the powder particles, and mix them evenly;

[0021] (3) Weigh a certain amount of dispersant, add a binder and a hydrophilic additive according to the corresponding mass fraction, mix and stir, and then add the three-dimensional graphene material and the lithium salt and mix and stir to obtain a uniform and viscous slurry;

[0022] (4) The slurry prepared in step (3) is disposed on the surface of the active material layer to form a uniform coating, and then dried to obtain the lithium metal composite negative electrode.

[0023] Optionally, the preparation method of the three-dimensional graphene material described in step (1) includes a self-assembly method, a cross-linking method, a chemical vapor deposition method, a template method and a 3D printing method, preferably a self-assembly method.

[0024] The self-assembly method for preparing three-dimensional graphene materials is simple to operate, has mild process conditions, and can accurately control the size, morphology and composition of the products. It is an effective means for large-scale preparation of three-dimensional graphene materials.

[0025] The cross-linking method is a method of promoting the formation of three-dimensional graphene structure by introducing divalent ions, metal oxides, small molecule monomers, etc. as cross-linking agents into graphene oxide. Although the preparation of three-dimensional graphene materials by the cross-linking method is simple to operate and requires mild conditions, the resulting three-dimensional structure is uneven in morphology and uncontrollable in size.

[0026] In the process of synthesizing three-dimensional graphene materials by chemical vapor deposition, CH4 / C2H4 / C2H2 / glucose, etc. are usually pyrolyzed and carbon deposited on a substrate at high temperature. After removing the substrate, three-dimensional graphene is obtained. However, the operation is complicated and the experimental impurity removal is difficult.

[0027] The template method is a method of combining graphene or graphene oxide derivatives onto a template and replicating the shape of the template to form a three-dimensional graphene structure. The template method has a simple preparation process, mild process conditions, and the three-dimensional structure formed is uniform and orderly, but the structure of the synthesized product depends on the structure of the template, and the preparation of some templates with specific structures is still difficult.

[0028] The 3D printing method can control the morphology and structure of the product three-dimensional graphene material by adjusting the morphology and microstructure of the template. It is a forward-looking method for achieving large-scale preparation of three-dimensional graphene materials in the future.

[0029] Optionally, the drying and dehumidification temperature in step (1) is 60-100° C., and the drying time is 1-5 h.

[0030] Optionally, the method for mixing the three-dimensional graphene material and the lithium salt in step (2) comprises ball milling, chemical precipitation, sol-gel method, ultrasonic mixing method, preferably ball milling.

[0031] Optionally, the ball milling speed of the ball milling method is 100-600 rpm, and the ball milling time is 3-6 h.

[0032] Optionally, the dispersant described in step (3) includes any one of N-methylpyrrolidone, tetrahydrofuran, dimethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, polyether ketone, or a combination of at least two thereof.

[0033] Optionally, the mass ratio of the three-dimensional graphene, lithium salt, binder, hydrophilic additive and dispersant in step (3) is (1-20): (1-5): (1-5): (0.5-2): (68-96), preferably (5-10): (2-3): (1-3): (0.5-1): (83-92).

[0034] Optionally, the mixing and stirring of the binder and the hydrophilic additive in step (3) is performed at a speed of more than 1100 rpm, and the stirring time is 1-20 hours.

[0035] Optionally, the speed of mixing and stirring the three-dimensional graphene and lithium salt in step (3) is above 1200 rpm, and the stirring time is 1-20 hours.

[0036] Optionally, the method of disposing the slurry of step (3) on the active material layer in step (4) includes any one of coating, film transfer, spraying, spin coating, roller pressing, and infiltration, or a combination of at least two thereof.

[0037] Optionally, the coating is disposed on the active material layer by a film transfer method, wherein the slurry is evenly coated on the surface of the release film, transferred to the surface of the active material layer, and vacuum dried at 50° C.-60° C. for 8-12 hours.

[0038] Another aspect of the present invention provides a solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode is the lithium metal composite negative electrode as described above.

[0039] Optionally, the active material of the positive electrode is any one of layered oxides, polyanion active materials, lithium-rich oxides or spinel oxides, or a combination of at least two thereof.

[0040] Optionally, the solid-state battery includes a lithium-sulfur solid-state battery, a bipolar solid-state battery, a sulfide solid-state battery, a polymer solid-state battery, a halide solid-state battery, an oxide solid-state battery, and an organic-inorganic composite solid-state battery.

[0041] Optionally, the solid-state battery is a bipolar solid-state battery, which is composed of n (n=2-20) layers stacked in a structure of "current collector-positive electrode-solid electrolyte-composite negative electrode-current collector-positive electrode-solid electrolyte-composite negative electrode".

[0042] The present invention has at least one of the following beneficial technical effects:

[0043] (1) A graphene space layer is set on the surface of the metal lithium negative electrode. The three-dimensional graphene in the space layer is mixed with lithium salt and adhesive to form a stable three-dimensional honeycomb skeleton structure, which can improve the mechanical strength of the negative electrode interface. Lithium ions are deposited in the skeleton structure or on the graphene space layer, which can realize lithium ion storage and regulate the uniform deposition of lithium ions, reduce the generation and growth of dendrites, and alleviate the expansion of lithium metal, thereby improving the cycle performance of metal lithium batteries.

[0044] (2) A graphene space layer is set on the surface of the metallic lithium negative electrode. The graphene space layer acts as an artificial SEI protective layer of the lithium metal negative electrode, isolating lithium from direct contact with the solid electrolyte, making metallic lithium compatible with a variety of solid electrolytes, reducing the occurrence of side reactions, and can be applied to a variety of solid-state batteries.

[0045] (3) The lithium metal composite negative electrode has a stable interface and is particularly suitable for application in solid-state batteries, especially bipolar solid-state batteries. The multilayer structure of bipolar solid-state batteries ensures cycle stability.

[0046] (4) The preparation method of lithium metal composite negative electrode is simple, easy and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A schematic diagram of lithium ion deposition when the lithium metal composite negative electrode of the present invention is applied to a solid-state battery;

[0048] Figure 2 A schematic diagram of the structure of the lithium metal composite negative electrode of the present invention applied to a bipolar solid-state battery;

[0049] Figure 3 is a SEM image of the three-dimensional graphene structure in the graphene space layer prepared in Example 1;

[0050] Figure 4 The cycle test curves of the lithium metal composite negative electrode in Examples 1, 2, 3 and Comparative Example 1 at a charge and discharge current of 0.3C;

[0051] Among them, 1-current collector, 2-positive electrode, 3-solid electrolyte, 4-space layer, 5-active material layer. DETAILED DESCRIPTION

[0052] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] The lithium metal composite negative electrode provided by the present invention is illustrated by way of example. Figure 1The lithium metal composite negative electrode comprises a space layer 4 and an active material layer 5 .

[0054] Figure 2 The overall structure is a schematic diagram of a bipolar solid-state battery, including n layers of repeated structural unit structures (2≤n≤20), each structural unit including a current collector 1, a positive electrode 2, a solid electrolyte 3, a space layer 4 and an active material layer 5.

[0055] Example 1

[0056] This embodiment provides a lithium metal composite negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a space layer;

[0057] The space layer has a pore size of 100 nm and a specific surface area of ​​2000 m 2 / g, three-dimensional graphene with a honeycomb skeleton structure with a yield strength of 20MPa, lithium hexafluorophosphate (LiPF6), polyethylene oxide (PEO), carboxymethyl cellulose (CMC), modifier polyethylene glycol (PEG), dispersant N-methylpyrrolidone (NMP), wherein the mass ratio of three-dimensional graphene, LiPF6, PEO, CMC, PEG, and NMP is 10:3:1:0.5:0.5:85. The thickness of the space layer is 5μm, the Young's modulus is 6GPa, the active site material layer is a 50μm lithium metal layer, and the current collector is copper foil.

[0058] The method for preparing the lithium metal composite negative electrode comprises the following steps:

[0059] (1) Preparation of three-dimensional graphene materials by self-assembly method: Graphene oxide (GO) is dispersed in water, and the GO dispersion is placed in a high-pressure reactor and heated at 120-180°C for 6-8 hours. The GO sheets are self-assembled into a three-dimensional honeycomb structure through hydrogen bonds and π-π interactions. The graphene material, LiPF6, PEO, and CMC are dried in a vacuum oven at 80°C for 3 hours;

[0060] (2) Weigh 10 g of three-dimensional graphene and 3 g of LiPF6 and put them into a ball mill at 500 rpm for 3 h to refine the powder particles and mix them evenly;

[0061] (3) Weigh 85 g of NMP, add 1 g of PEO, 0.5 g of CMC, and 0.5 g of PEG, stir at 1100 rpm for 12 h, then add the powder mixed evenly in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;

[0062] (4) The slurry of step (3) is transferred to the surface of the active material layer to form a uniform coating, and then dried under vacuum at 50°C for 8 hours, and then cooled to room temperature to obtain the lithium metal composite negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.

[0063] Example 2

[0064] This embodiment provides a lithium metal composite negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a space layer;

[0065] The space layer has a pore size of 200nm and a specific surface area of ​​2000m 2 / g, three-dimensional graphene with a honeycomb skeleton structure with a yield strength of 16MPa, lithium bis(fluorosulfonyl)imide (LiFSI), polystyrene butadiene copolymer (SBR), carboxymethyl cellulose (CMC), modifier sodium dodecylbenzene sulfonate (SDBS), dispersant ethylene glycol dimethyl ether (DME), wherein the mass ratio of three-dimensional graphene, LiFSI, SBR, CMC, SDBS, and DME is 10:3:1:0.5:0.5:85. The thickness of the space layer is 5μm, the Young's modulus is 6GPa, the active site material layer is a 50μm lithium metal layer, and the current collector is copper foil.

[0066] The method for preparing the lithium metal composite negative electrode comprises the following steps:

[0067] (1) Preparation of three-dimensional graphene materials by self-assembly method: Graphene oxide (GO) is dispersed in water, and the GO dispersion is placed in a high-pressure reactor and heated at 120-180°C for 6-8 hours. The GO sheets are self-assembled into a three-dimensional honeycomb structure through hydrogen bonds and π-π interactions. The graphene material, LiFSI, SBR, and CMC are dried in a vacuum drying oven at 80°C for 3 hours;

[0068] (2) Weigh 10 g of three-dimensional graphene and 3 g of LiFSI and put them into a ball mill at 500 rpm for 3 h to refine the powder particles and mix them evenly;

[0069] (3) Weigh 85 g of DME, add 1 g of SBR, 0.5 g of CMC, and 0.5 g of SDBS, stir at 1100 rpm for 12 h, then add the powder mixed evenly in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;

[0070] (4) The slurry of step (3) is transferred to the surface of the active material layer to form a uniform coating, and then dried under vacuum at 50°C for 8 hours, and then cooled to room temperature to obtain the lithium metal composite negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.

[0071] Example 3

[0072] This embodiment provides a lithium metal composite negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a space layer;

[0073] The space layer has a pore size of 300nm and a specific surface area of ​​3000m2 / g, three-dimensional graphene with a honeycomb skeleton structure with a yield strength of 10MPa, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyvinylidene fluoride (PVDF), triethyl phosphate (TEP), modifier 1-methylimidazole chloride, dispersant dimethyl carbonate, wherein the mass ratio of three-dimensional graphene, LiTFSI, PVDF, TEP, 1-methylimidazole chloride, and dimethyl carbonate is 5:3:2:0.5:0.5:89. The thickness of the space layer is 5μm, the Young's modulus is 6GPa, the active site material layer is a 50μm lithium metal layer, and the current collector is copper foil.

[0074] The method for preparing the lithium metal composite negative electrode comprises the following steps:

[0075] (1) Preparation of three-dimensional graphene materials by self-assembly method: Graphene oxide (GO) is dispersed in water, and the GO dispersion is placed in a high-pressure reactor and heated at 120-180°C for 6-8 hours. The GO sheets are self-assembled into a three-dimensional honeycomb structure through hydrogen bonds and π-π interactions. The graphene material, LiTFSI, and PVDF are dried in a vacuum oven at 80°C for 3 hours;

[0076] (2) Weigh 5 g of three-dimensional graphene and 3 g of LiTFSI and put them into a ball mill at 500 rpm for 3 h to refine the powder particles and mix them evenly;

[0077] (3) Weigh 89 g of dimethyl carbonate, add 2 g of PVDF, 0.5 g of TEP, and 0.5 g of 1-methylimidazole chloride, stir at 1100 rpm for 12 h, then add the powder mixed in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;

[0078] (4) The slurry of step (3) is transferred to the surface of the active material layer to form a uniform coating, and then dried under vacuum at 50°C for 8 hours, and then cooled to room temperature to obtain the lithium metal composite negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.

[0079] Example 4

[0080] Compared with Example 1, the only difference is that the mass ratio of three-dimensional graphene to the slurry is replaced with 20%, and the other conditions remain unchanged.

[0081] Example 5

[0082] Compared with Example 1, the only difference is that the mass ratio of three-dimensional graphene to the slurry is replaced with 1%, and the other conditions remain unchanged.

[0083] Example 6

[0084] Compared with Example 1, the only difference is that the mass ratio of LiPF6 in the slurry is replaced by 5%, and the other conditions remain unchanged.

[0085] Example 7

[0086] Compared with Example 1, the only difference is that the mass ratio of LiPF6 in the slurry is replaced with 1%, and the other conditions remain unchanged.

[0087] Example 8

[0088] Compared with Example 1, the only difference is that the mass ratio of PEO in the slurry is replaced by 5%, and the other conditions remain unchanged.

[0089] Example 9

[0090] Compared with Example 1, the only difference is that the mass ratio of PEO in the slurry is replaced by 1%, and the other conditions remain unchanged.

[0091] Example 10

[0092] Compared with Example 1, the only difference is that the mass ratio of CMC+PEG in the slurry is replaced with 2%, and the other conditions remain unchanged.

[0093] Embodiment 11

[0094] Compared with Example 1, the only difference is that the mass ratio of CMC+PEG in the slurry is replaced with 0.5%, and the other conditions remain unchanged.

[0095] Example 12

[0096] Compared with Example 1, the only difference is that the thickness of the space layer is replaced with 1 μm, and the other conditions remain unchanged.

[0097] Embodiment 13

[0098] Compared with Example 1, the only difference is that the thickness of the space layer is replaced with 50 μm, and the other conditions remain unchanged.

[0099] Embodiment 14

[0100] Compared with Example 1, the only difference is that the thickness of the active material layer is replaced with 5 μm, and the other conditions remain unchanged.

[0101] Embodiment 15

[0102] Compared with Example 1, the only difference is that the thickness of the active material layer is replaced with 100 μm, and the other conditions remain unchanged.

[0103] Example 16

[0104] Compared with Example 1, the only difference is that the lithium metal strip of the active material layer is replaced by a lithium aluminum alloy strip, and the other conditions remain unchanged.

[0105] Embodiment 17

[0106] Compared with Example 1, the only difference is that 10 g of three-dimensional graphene and 3 g of LiPF6 are weighed and mixed using an ultrasonic mixing method, and the other conditions remain unchanged.

[0107] Embodiment 18

[0108] Compared with Example 1, the only difference is that the space layer is disposed on the active material layer by coating, and a 50 μm coating blade is used on the coater to evenly coat the space layer slurry on the active material layer at a speed of 25 m / min, and other conditions remain unchanged.

[0109] Embodiment 19

[0110] Compared with Example 1, the only difference is that the method for preparing three-dimensional graphene is replaced by chemical vapor deposition: prepare a foam nickel substrate, put the treated substrate into the central heating zone of the CVD reactor, start the vacuum pump, heat the reactor to 800°C at a rate of 5-20°C / min and keep it for 60 minutes, introduce methane gas and hydrogen at the same time, grow graphene on the substrate for 60 minutes, and cool it down naturally. The other conditions remain unchanged.

[0111] Embodiment 20

[0112] Compared with Example 1, the only difference is that the prepared lithium metal composite negative electrode is used to assemble a bipolar battery.

[0113] Comparative Example 1

[0114] This comparative example provides an all-solid-state battery, which directly uses a 50 μm lithium metal strip as the negative electrode.

[0115] Comparative Example 2

[0116] This comparative example provides an all-solid-state battery, which directly uses a 50 μm lithium aluminum alloy strip as the negative electrode.

[0117] Comparative Example 3

[0118] This comparative example provides an all-solid-state battery. Compared with Example 1, no three-dimensional graphene is added to the lithium metal composite negative electrode thereof, and the other conditions are the same as those of Example 1.

[0119] Comparative Example 4

[0120] This comparative example provides an all-solid-state battery. Compared with Example 1, no lithium salt is added to the lithium metal composite negative electrode thereof, and the other conditions are the same as those of Example 1.

[0121] Comparative Example 5

[0122] This comparative example provides an all-solid-state battery. Compared with Example 1, no binder is added to the lithium metal composite negative electrode thereof, and the other conditions are the same as those of Example 1.

[0123] Comparative Example 6

[0124] This comparative example provides an all-solid-state battery. Compared with Example 1, no additive is added to the lithium metal composite negative electrode thereof, and the other conditions are the same as those of Example 1.

[0125] Comparative Example 7

[0126] This comparative example provides an all-solid-state battery. Compared with Example 1, its lithium metal composite negative electrode space layer is replaced by a graphene nanosheet coating, and the other conditions are the same as those of Example 1.

[0127] Comparative Example 8

[0128] This comparative example provides an all-solid-state battery. Compared with Example 1, its anti-dendrite negative electrode structure space layer is replaced by a transferred Al2O3 coating, and the other conditions are the same as Example 1.

[0129] Comparative Example 9

[0130] This comparative example provides a bipolar solid-state battery, whose anti-dendrite negative electrode configuration is the same as that of comparative example 1.

[0131] Preparation of all-solid-state batteries:

[0132] The battery produced is a mold battery with an electrode active area of ​​0.8 cm 2 .

[0133] The preparation method of the solid electrolyte is as follows: 100 mg of lithium phosphorus sulfur chloride sulfide (LSPCl) electrolyte is taken and pressed into a Teflon tablet pressing mold at a pressure of 300 MPa to prepare an electrolyte layer;

[0134] The preparation method of the positive electrode is as follows: 20 mg LiNi 0.8 Co 0.1 Mn 0.1 O2, small-particle LSPCl electrolyte, and carbon black are uniformly mixed in a mass ratio of 75:25:2, and pressed into a Teflon tablet pressing mold at a pressure of 300 MPa to obtain a positive electrode sheet of the battery;

[0135] The preparation method of the all-solid-state battery is as follows: the prepared positive electrode sheet is pressed on one side of the LSPCl electrolyte at a pressure of 300MPa, and then the functional lithium metal negative electrode is pressed on the other side of the electrolyte layer at 20MPa to prepare the all-solid-state battery.

[0136] The preparation method of the bipolar solid-state battery is as follows: the prepared positive electrode sheet is pressed on one side of the solid electrolyte layer at a pressure of 300MPa, and the functional lithium metal negative electrode is pressed on the other side of the electrolyte layer to obtain a layer of repeating structural units. The current collector is placed between multiple repeating structural units, the repeating structural units are stacked, and an external pressure of 20MPa is applied to assemble into a bipolar solid-state battery.

[0137] Solid-state battery negative electrode performance test:

[0138] The negative electrodes provided in Examples 1-19 and Comparative Examples 1-8 were respectively assembled into solid-state batteries for cycle performance testing. The specific testing method is: at 25°C, constant current charging and constant current discharging were adopted, the charge and discharge voltage range was 2.7-4.3V, the charge and discharge rate was 0.3C or 2C, the initial capacity of the battery was recorded as C0, and the battery completed a full charge and discharge, which was recorded as a cycle; charging and discharging were performed according to the above method, and the capacity of the battery after each cycle was tested until the capacity of the battery was 80% of C0 or the battery short-circuited or the charge and discharge efficiency was lower than 98%, and the number of cycles at this time was recorded.

[0139] The negative electrodes provided in Example 20 and Comparative Example 9 were respectively assembled into bipolar solid-state batteries for cycle performance testing. The specific testing method is: at 25°C, constant current charging and constant current discharging were adopted, the charge and discharge voltage range was 5.0-8.5V, the charge and discharge rate was 0.3C or 2C, the initial capacity of the battery was recorded as C1, and the battery completed a full charge and discharge, which was recorded as a cycle; charging and discharging were performed according to the above method, and the capacity of the battery after each cycle was tested until the capacity of the battery was 80% of C1 or the battery short-circuited or the charge and discharge efficiency was lower than 98%, and the number of cycles at this time was recorded.

[0140] Young's modulus test:

[0141] The space layer is set on the lithium metal negative electrode, and the Young's modulus test is performed on the negative electrode interface. Using an atomic force microscope, one end of the microcantilever, which is extremely sensitive to weak forces, is fixed, and the other end has a tiny needle tip. The needle tip gently contacts the interface, and the repulsive force between the needle tip and the interface is controlled to be constant during scanning. The microcantilever with the needle tip will fluctuate perpendicular to the interface direction corresponding to the equipotential surface of the force between the needle tip and the interface atoms. Using optical detection or tunnel current detection, the position change of the microcantilever corresponding to each scanning point can be measured, so that the sample morphology can be obtained and the Young's modulus can be calculated.

[0142] The cycle performance test results of the all-solid-state battery assembled with the functional lithium metal negative electrodes prepared in Examples 1-20 and Comparative Examples 1-9 are shown in Table 1.

[0143] Table 1 Battery cycle performance test results

[0144]

[0145]

[0146] Battery cycle performance test analysis results:

[0147] (1) Comparison between Examples 1-3 and Comparative Example 1

[0148] Examples 1-3 show that adding a space layer of the present invention to the surface of a lithium metal negative electrode improves the cycle performance of an all-solid-state battery. The space layer of Examples 1-3 is composed of three-dimensional graphene, lithium salt, a binder and an additive, such as Figure 1 As shown in the schematic diagram, the three-dimensional porous structure can conduct lithium ions while storing lithium ions. Figure 3 This is a SEM image of three-dimensional graphene after magnification 1500 times. It can be seen from the figure that three-dimensional graphene is a porous structure with uniform pore distribution and a honeycomb shape. It can form a stable structure when combined with a binder and has the function of storing lithium ions. Compared with the use of pure lithium metal strip as the negative electrode in comparative example 1, the lithium metal negative electrode with an additional space layer has greatly improved the cycle performance of the battery at both 0.3C and 2C charge and discharge rates. According to Table 1 and Figure 4 According to the data, at a charge and discharge rate of 0.3C, pure lithium ribbon can only cycle 60 times, while lithium metal composite negative electrode can cycle 210 times; at a charge and discharge rate of 2C, pure lithium ribbon can cycle 30 times, while lithium metal composite negative electrode can cycle 163 times. This shows that the combination of three-dimensional graphene, lithium salt and binder can stably conduct lithium ions during battery cycling, regulate the uniform deposition of lithium ions, reduce the growth of lithium dendrites caused by stress concentration, and increase the cycle life of the battery.

[0149] (2) Comparison between Example 1 and Examples 4-15

[0150] Examples 4-15 show the effects of changes in the content of three-dimensional graphene, lithium salts, binders, and hydrophilic additives in the space layer on the cycle life of all-solid-state batteries. From the data in Table 1, it can be seen that the three-dimensional graphene content is too high, it is not easy to disperse in the dispersant, it is easy to produce precipitation, the space layer formed has dense pores, lithium ion shuttle is complex, and the interface impedance increases; the three-dimensional graphene content is low, the three-dimensional network structure is loose, and the storage of lithium ions is small, which will affect the cycle performance of the battery. The content of lithium salts, binders, and hydrophilic additives is too high or too low, which will affect the stability of the three-dimensional graphene structure and the mobility of lithium ions, thereby reducing the cycle performance of the battery. In addition, the thickness of the space layer and the thickness of the active material layer should also be accurately controlled. The thickness of the space layer is too thick, the interface impedance of the lithium metal battery increases, and the battery energy density is affected; the thickness of the space layer is too thin, the lithium storage space is small, and the protection effect on the lithium negative electrode interface is weak. It can be seen from this that the content between the materials in the space layer in the present invention and the thickness of the space layer and the active material layer should be adjusted and determined to ensure excellent results.

[0151] (3) Comparison between Example 1 and Examples 17-19

[0152] Examples 17-19 show the effects of different mixing processes, coating processes, and three-dimensional graphene preparation methods on the performance of all-solid-state batteries. Example 17 uses different powder mixing methods to mix the solid powders evenly, which has little effect on the battery cycle performance. Example 18 replaces the transfer method with a coating method. The coating method needs to ensure the uniformity of the space layer coated on the active material layer and control the surface tension of the lithium metal strip during the drying process. Example 19 replaces different methods for preparing three-dimensional graphene. The three-dimensional graphene prepared by different methods needs to ensure the porosity and stability of the porous structure so that the space layer can store a large amount of lithium ions.

[0153] (4) Comparison between Example 16 and Comparative Example 2

[0154] Example 16 and Comparative Example 2 show the effect of setting a space layer on the lithium alloy layer on the cycle performance of the all-solid-state battery. Compared with pure metal lithium, the lithium alloy layer is doped with one or more metal elements to improve the hardness, conductivity and cycle performance of metal lithium. From the data in Table 1, after setting a space layer on the alloy layer, the cycle performance of the lithium metal battery is improved. At a charge and discharge rate of 0.3C, the cycle is improved by 136 cycles, and at a charge and discharge rate of 2C, the cycle is improved by 116 cycles.

[0155] (5) Comparison between Example 1 and Comparative Examples 3-6

[0156] Comparative Examples 3-6 show the importance of the space layer composition materials provided by the present invention, and the influence of different materials on the cycle performance of all-solid-state batteries. From the data in Table 1, the lack of different space layer materials will reduce the cycle of the battery, and the battery cycle performance will be less improved compared with pure lithium ribbon.

[0157] (6) Comparison between Example 1 and Comparative Examples 7-8

[0158] Comparative Examples 7-8 show the effect of replacing the space layer material with graphene nanosheets and inorganic coatings on the performance of all-solid-state batteries. The space layer material provided by the present invention forms a honeycomb porous structure, which can regulate lithium ion deposition, reduce lithium dendrite growth, alleviate lithium metal expansion, improve lithium ion conduction, improve interface mechanical strength, and set lithium ion storage space. After being replaced with graphene sheets, the two-dimensional structure reduces the space for storing lithium ions, and the inorganic Al2O3 coating can only improve the interface mechanical strength and inhibit dendrite growth, but has no effect on regulating lithium ion deposition, and has little effect on improving the cycle performance of lithium metal batteries.

[0159] (7) Comparison between Example 20 and Comparative Example 9

[0160] Example 20 and Comparative Example 9 show that the space layer provided by the present invention is applied to a bipolar battery to improve the cycle performance of the bipolar battery. As can be seen from Table 1, at a charge and discharge rate of 0.3C, the battery cycle is improved by 116 cycles, and at a charge and discharge rate of 2C, the battery cycle is improved by 98 cycles. The space layer isolates and reduces the side reactions that occur when lithium metal directly contacts the solid electrolyte, while improving the consistency of the multi-layer interface, inhibiting dendrite growth and regulating the deposition of lithium ions, and the cycle improvement effect is obvious.

[0161] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A lithium metal composite negative electrode, characterized in that: The negative electrode includes an active material layer and a graphene space layer disposed on and in contact with the active material layer; Wherein, the active material layer is a lithium metal and / or lithium alloy layer; The graphene space layer is a layer of a three-dimensional porous structure comprising three-dimensional graphene, lithium salt, a binder and a hydrophilic additive, wherein the three-dimensional graphene has a honeycomb skeleton structure, the pore size of the three-dimensional graphene is 1-500nm, and the specific surface area is 500-5000m 2 / g, yield strength is 10-50MPa; The graphene space layer has a thickness of 1-100 μm and a Young's modulus of ≥6 GPa.

2. The lithium metal composite negative electrode according to claim 1, characterized in that The lithium salt includes any one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium difluorooxalatoborate, lithium dimethyl borate, lithium bis(fluorosulfonyl imide), lithium tetrafluoroborate, lithium difluorophosphate, and lithium 4,5-dicyano-2-trifluoromethylimidazole, or a combination of at least two thereof; The binder comprises one or a combination of at least two of polyvinyl alcohol, polyethylene oxide, polybutylene styrene, polystyrene butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxycellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organic siloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and derivatives thereof; The hydrophilic additives include thickeners and modifiers; The thickener includes one or more of carboxymethyl cellulose, sesbania gum, sodium starch phosphate, triethyl phosphate, and sodium polyacrylate; The modifier includes one or more combinations of polyethylene glycol, polyvinyl alcohol, polyoxyethylene ether, carboxylates, sulfonates, sulfate esters, phosphate esters, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids; The mass ratio of the three-dimensional graphene, lithium salt, binder and hydrophilic additive is (1-20): (1-5): (1-5): (0.5-2).

3. The lithium metal composite negative electrode according to claim 1, characterized in that The active material layer includes a metal lithium layer, a lithium alloy layer, or a combination of the two; wherein the lithium alloy layer includes an alloy of lithium and one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt; The thickness of the active material layer is 3 μm-300 μm; The thickness ratio of the graphene space layer to the active material layer is (0.001-1):

1.

4. The lithium metal composite negative electrode according to claim 1, characterized in that The lithium metal composite negative electrode also includes a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and an organic fiber film with a metal plated surface.

5. A method for preparing a lithium metal composite negative electrode as claimed in any one of claims 1 to 4, characterized in that: The method comprises: (1) preparing three-dimensional graphene materials, drying and dehumidifying the three-dimensional graphene, lithium salt, binder, and hydrophilic additive; (2) Weigh corresponding proportions of three-dimensional graphene and lithium salt, mix them, refine the powder particles, and mix them evenly; (3) Weigh a certain amount of dispersant, add a binder and a hydrophilic additive according to the corresponding mass fraction, mix and stir, and then add three-dimensional graphene and lithium salt and mix and stir to obtain a uniform and viscous slurry; (4) The slurry prepared in step (3) is disposed on the surface of the active material layer to form a uniform coating, and then dried to obtain the lithium metal composite negative electrode.

6. The method according to claim 5, characterized in that The preparation method of the three-dimensional graphene material described in step (1) includes self-assembly method, cross-linking method, chemical vapor deposition method, template method and 3D printing method.

7. The method according to claim 5 or 6, characterized in that: The method for mixing the three-dimensional graphene and the lithium salt in step (2) includes ball milling, chemical precipitation, sol-gel method, and ultrasonic mixing method; The dispersant in step (3) includes any one of N-methylpyrrolidone, tetrahydrofuran, dimethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, polyether ketone, or a combination of at least two thereof; The mass ratio of the three-dimensional graphene, lithium salt, binder, hydrophilic additive and dispersant in step (3) is (1-20): (1-5): (1-5): (0.5-2): (68-96); The mixing and stirring of the binder and the hydrophilic additive in step (3) is performed at a speed of more than 1100 rpm and a stirring time of 1-20 hours; The speed of stirring the three-dimensional graphene and lithium salt in step (3) is above 1200 rpm, and the stirring time is 1-20 hours.

8. The method according to claim 5, characterized in that The method of disposing the slurry of step (3) on the active material layer in step (4) includes any one of coating, film transfer, spraying, spin coating, roller pressing, and immersion, or a combination of at least two of them.

9. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode is a lithium metal composite negative electrode as described in any one of claims 1 to 4, and the active material of the positive electrode is any one of layered oxides, polyanion active materials, lithium-rich oxides or spinel oxides, or a combination of at least two thereof; the solid-state battery comprises a lithium-sulfur solid-state battery, a bipolar solid-state battery, a sulfide solid-state battery, a polymer solid-state battery, a halide solid-state battery, an oxide solid-state battery, and an organic-inorganic composite solid-state battery.

Citation Information

Patent Citations

  • Negative pole piece as well as preparation method and application thereof

    CN119181765A

  • Three-dimensional porous graphene and application thereof in lithium ion battery

    CN111825080A

  • Composite metal lithium negative electrode capable of slowing down consumption of lithium salt and preparation method of composite metal lithium negative electrode

    CN113346046A

  • Solid-state composite metal lithium negative electrode with high electron / ion transmission characteristic as well as preparation method and application of solid-state composite metal lithium negative electrode

    CN114171716A

  • Carbon material, anode material and spacer additive for lithium ion battery

    US20170283265A1

Cited By

  • Solid-state battery, preparation method thereof and power utilization device

    CN121076266A

  • Solid-state battery and preparation method therefor, and electric device

    CN121076266B

  • Negative pole piece for solid-state battery, solid-state battery and manufacturing method of negative pole piece

    CN121215684A